Chemical composition and size-fractionated origins of aerosols over a remote coastal site in southern Taiwan - Ying I. Tsai (2018)
© Taiwan Association for Aerosol Research. In spring 2013 air samples were collected from a coastal site in the sparsely populated far south-west of Taiwan and analysed for ambient gases, inorganic salts, carboxylates, and saccharides. Concentration of ambient gases was in the order SO 2 > HC l > HNO 3 > NH 3 > HNO 2 . Day-night variation in concentrations indicated that photochemical conversion of HNO 2 to HNO 3 occurs during the day. PM 2.5 (16.16 ± 5.30 μg m –3 ) accounted for 61.1% of PM10 mass concentrations. The main inorganic salts were SO 4 2– , NH 4 + , Na + , NO 3 - , and Cl - , collectively accounting for 48.8 ± 27.4% of the PM 2.5 . Cldepletion during the day was higher than during the night due to the presence of reactive photochemical products. The average Cl-depletion of PM 2.5 (53.1%) was markedly higher than that of PM 2.5-10 (26.0%), indicating that in PM 2.5 , a high amount of Cl - reacts with acidic gases to form HCl, which then escapes into the atmosphere. The carboxylate concentration in PM 2.5 was 0.50 ± 0.24 μg m -3 . It was found that low-molecular-weight carboxylates formed more readily in the open coastal region than in urban regions of southern Taiwan. Additionally, the daily mean ratio of Oxalate/non-seasalt SO 4 2- (6.15 ± 2.28%) in the coastal region was higher than that in the urban regions in southern Taiwan. The most prevalent saccharide in PM 2.5 was myo-inosital (333 ± 300 μg m -3 ), a type of soil fungus metabolite. Emissions of arabitol and mannitol, emitted through lichen and fungal activity, were markedly higher during the day. Only a trace amount (8.92 ± 16.92 μg m -3 ) of Levoglucosan (Levo), an indicator of biomass burning, was detected. The mean Levo/organic carbon ratio was 5.04 ± 8.72‰, suggesting that biomass burning contributed slightly to aerosols in the study area. An analysis of air mass backward trajectories showed that the products of biomass burning in Southeast Asia and southern China may be transported to the study area through long-range transport. This effect is more noticeable during the day when onshore breezes support the transport of particles sourced from the west of Taiwan.